Developmental and temporal changes in petunia petal transcriptome reveal scent-repressing plant-specific RING–kinase–WD40 protein - Shor, Ekaterina; Skaliter, Oded; Sharon, Elad; Kitsberg, Yaarit; Bednarczyk, Dominika; Kerzner, Shane; Vainstein, Danny; Tabach, Yuval; Vainstein, Alexander (Frontiers in Plant Science, 2023)
In moth-pollinated petunias, production of floral volatiles initiates when the flower opens and occurs rhythmically during the day, for optimal flower–pollinator interaction. To characterize the developmental transcriptomic response to time of day, we generated RNA-Seq databases for corollas of floral buds and mature flowers in the morning and in the evening. Around 70% of transcripts accumulating in petals demonstrated significant changes in expression levels in response to the flowers’ transition from a 4.5-cm bud to a flower 1 day postanthesis (1DPA). Overall, 44% of the petal transcripts were differentially expressed in the morning vs. evening. Morning/evening changes were affected by flower developmental stage, with a 2.5-fold larger transcriptomic response to daytime in 1DPA flowers compared to buds. Analyzed genes known to encode enzymes in volatile organic compound biosynthesis were upregulated in 1DPA flowers vs. buds—in parallel with the activation of scent production. Based on analysis of global changes in the petal transcriptome, PhWD2 was identified as a putative scent-related factor. PhWD2 is a protein that is uniquely present in plants and has a three-domain structure: RING–kinase–WD40. Suppression of PhWD2 (termed UPPER - Unique Plant PhEnylpropanoid Regulator) resulted in a significant increase in the levels of volatiles emitted from and accumulated in internal pools, suggesting that it is a negative regulator of petunia floral scent production.